Religion, culture and conscience - Hordern, J (Elsevier, 2020)
Religion, belief and culture should be recognized as potential sources of moral purpose and personal strength in healthcare, enhancing the welfare of both clinicians and patients amidst the experience of ill-health, healing, suffering and dying. Communication between doctors and patients and between healthcare staff should attend sensitively to the welfare benefits of religion, belief and culture. Doctors should respect personal religious and cultural commitments, taking account of their significance for treatment and care preferences. Good doctors understand their own beliefs and those of others. They hold that patient welfare is best served by understanding the importance of religion, belief and culture to patients and colleagues. The sensitive navigation of differences between people's religions, beliefs and cultures is part of doctors' civic obligations and in the UK should follow the guidance of the General Medical Council and Department of Health and Social Care. In particular, apparent conflict between clinical judgement or normal practices and a patient's culture, religion and belief should be considered carefully. Doctors' own religion or culture may play an important role in promoting adherence to this good practice. In all matters, doctors' conduct should be governed by the law and arrangements for conscientious objection that are in effect. The strongest ethical arguments in favour of conscientious objection provisions concern the moral integrity of professionals, the objectives and values of the medical profession, the nature of healthcare in liberal democracy and the welfare of patients. In practice, arguments mounted against conscientious objection have not been found persuasive.